2008
DOI: 10.1016/j.taap.2007.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Subhepatotoxic exposure to arsenic enhances lipopolysaccharide-induced liver injury in mice

Abstract: Exposure to arsenic via drinking water is a serious health concern in the US. Whereas studies have identified arsenic alone as an independent risk factor for liver disease, concentrations of arsenic required to damage this organ are generally higher than found in the US water supply. The purpose of the current study was to test the hypothesis that arsenic (at subhepatotoxic doses) may also sensitize the liver to a second hepatotoxin. To test this hypothesis, the effect of chronic exposure to arsenic on liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 40 publications
6
35
0
Order By: Relevance
“…Therefore, OFC may also be protecting against damage in this model by preventing hepatic sensitization caused by HFD-induced endotoxemia. Such a mechanism is supported by previous studies that arsenic-exposed livers are more sensitive to exogenous LPS (47) and that liver injury here in OFC-fed mice was insensitive to arsenic administration.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Therefore, OFC may also be protecting against damage in this model by preventing hepatic sensitization caused by HFD-induced endotoxemia. Such a mechanism is supported by previous studies that arsenic-exposed livers are more sensitive to exogenous LPS (47) and that liver injury here in OFC-fed mice was insensitive to arsenic administration.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, Pinyayev et al showed that bacteria from the mouse cecum can metabolize arsenic (141) and others have shown that the human gut flora can metabolize arsenic into toxic metabolites (142,143). Whereas this is distinctly possible, it should be noted that concentrations that are 10-fold higher than used here were not directly hepatotoxic (47). Alternatively, the effects of arsenic on the microbiome may mediate the observed hepatotoxicity.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…A high fat diet enchanced arsenic-induced liver fibrosis in this study and caused an array of related aberrant gene expression changes [36]. Arteel et al demonstrated similar results using four to 6 week-old C57BLl6J mice were exposed to 49 ppm arsenic as sodium arsenite in drinking water for seven months [37]. They showed AL T and AST levels were significantly increased 2 and 3 fold, respectively in response to lipopolysaccharide (LPS) challenge.…”
Section: Mechanisms Of Arsenic-induced Atherosclerosissupporting
confidence: 69%